RAGASA NG BUFFALO: Kuwento at Pakikibaka ng Bukidnon Free Farmers and Agricultural Laborers Association - Vallejos, Celeste Francisco; Vallejos, Reginald S. (Philippine Journal of Social Development; 2008, 2010)
This article is a documentation of community organizing written from the point of view of the peasants of BUFFALO in Bukidnon. It shares the struggles of a peasant organization in building and sustaining collective actions in pursuit of genuine agrarian reform. BUFFALO celebrated its 21st founding anniversary on February 2008. Two decades of struggle taught them that through militancy and collective action, they can overcome any challenge that will come their way. This documentation also reflects BUFFALO’s own assessment of their organization and the lessons they learned from their two decades of organizing work.